[President Robert E. Kennedy & Dean Everett Chandler speaking], March 3, 1978 - P. K. Phillips::::::photographer::: (1978)
President Robert E. Kennedy and Dean Everett Chandler speaking to a group. This presumably took place at a ceremony regarding the commemoration or ground breaking of Kennedy Library.